Enterocutaneous fistulae: Etiology, treatment, and outcome - A study from South India - Prakash Kumar; Nanda K Maroju; Vikram Kate (The Saudi Journal of Gastroenterology, 2011)
Background/Aim: Enterocutaneous fistula (ECF) is a difficult condition managed in the surgical wards and is associated with significant morbidity and mortality. Sepsis, malnutrition, and electrolyte abnormality is the classical triad of complications of ECF. Sepsis with malnutrition is the leading cause of death in cases of ECF. Although it is a common condition, no recent report in literature on the profile of patients with ECF has been documented from the southern part of India. Materials and Methods: All consecutive patients who developed or presented with ECF during the study period were included in the study. The etiology, anatomic distribution, fistula output, clinical course, complications, predictive factors for spontaneous closure, and outcomes for patients with ECF were studied. Results: A total of 41 patients were included in this prospective observational study, of which 34 were males and 7 were females. About 95% of ECF were postoperative. Ileum was found to be the most common site of ECF. Also, 49% of fistulas were high output and 51% were low output. Serum albumin levels correlated significantly with fistula healing and mortality. Surgical intervention was required in 41% of patients. Conclusion: Most of the ECF are encountered in the postoperative period. Serum albumin levels can predict fistula healing and mortality. Conservative management should be the first line of treatment. Mortality in patients with ECF continues to be significant and is commonly related to malnutrition and sepsis.